Trend in dietary calcium intake among elderly in Kuantan, Pahang - Zamzuri, Maisalihah; Hamirudin, Aliza Haslinda; Zainudin, Norain; Sidek, Suriati; A. Rahman, Nor Azlina (2019)
Introduction: Dietary calcium intake is important in body system regulation. Inadequate intake among elderly may lead to various health issues such as osteoporosis and hip fracture. In order to counter the problem, this study was carried out to identify dietary calcium intake among elderly in Kuantan, Pahang. Methods: A face to face interviewer-administered session was done individually with seventy-nine (n=79) subjects aged ≥60 years to collect data on sociodemographic background, health status and dietary intake. Diet history method was used to obtain information related to dietary intake and analyzed using Nutritionist Pro Software. P-value was set at p<0.05 as statistically significant. Results: Almost all elderly subjects had dietary calcium intake lower than recommendation, which was 92.4%, and only 7.6% of total elderly met the recommended intake. This study found that the mean dietary calcium intake was 421.7 + 344.3 mg/day which is lower than Recommended Nutrient Intakes (RNI) for Malaysian. Mean calcium intake was significantly lower than RNI in both gender (p<0.001). The difference of calcium intake between male and female elderly was not significant; with mean dietary calcium intake for male and female were 414.2 + 344.3 mg/day and 426.0 + 347.8 mg/day, respectively. From the analysis, dietary calcium intake in elderly from non-dairy sources (228.4 + 149.3 mg) is higher than dairy sources (median (IQR)= 0.0 (326.0) 5mg). Conclusions: In conclusion, inadequate dietary calcium is an issue among elderly people in Kuantan which may lead to several health problems. Hence, appropriate strategies need to be taken in order to ensure optimum nutritional status among this at risk population.